Electrodeposition of Cu on CoTa Barrier in the Alkaline CuSO4-Ethylenediamine Solution. Issue 6 (2nd June 2021) - Qiu, Li-Na; Wang, Xu; Hu, Chun-Feng; Qu, Xin-Ping
Abstract : Direct Cu electroplating on the Cox Tay layers in an alkaline CuSO4 -Ethylenediamine (En) solution was carried out and the effects of plating time, plating potential and current density on the film properties were investigated. The electrodeposition mechanism of Cu in CuSO4 -En solution at different pH values was systematically studied by cyclic voltammetry and electrochemical quartz crystal microgravimetry in combination with UV–visible spectrophotometry. The deposition mechanism of Cu in the electrolyte is closely related to pH value. At pH 5, the predominant reaction is the reduction of Cu 2+ to metallic Cu; at pH 7 and pH 9, the predominant reactions are the reduction of CuEn2 2+ to metallic Cu. Results also show that increasing plating current density or potential can effectively increase Cu nucleation density on the Cox Tay . A high nucleation density (about 2.2 × 10 11 cm −2 ) of Cu on Co1 Ta1 is obtained. The electroplated Cu film has a relatively strong (111) preferred orientation. These results suggest that the direct Cu electroplating on the Co1 Ta1 alloy barrier with higher anti-corrosion than Co in the alkaline solution and high nucleation density provides a new approach for the future Cu interconnect.